Review of effectiveness of the foreign medical team employment in Nepal Earthquake, 2015. (2017)
SUMMARY: Background Nepal experienced a massive earthquake on 25th April, 2015 measuring 7.8 Richter scale followed by large aftershock on 12th May that further added to the destruction, especially in Sindhupalchowk and Dolakha. On request of Government of Nepal, international community extended financial and technical assistance to overcome the impact of the earthquake. Foreign Medical Teams (FMTs); now known as emergency medical team, from different countries and volunteers from within the country had helped in health service delivery. Although Nepal had experienced devastating earthquake in 1990 BS and earlier the working procedure responding to the earthquake at that time were not well documented. So, the need for documenting the working procedure and the effectiveness in response to post-earthquake scenario was realized so that it can be a lesson for future events of such nature. Thus, a thorough review of the effectiveness (especially their deployment, functionality, perspectives of the district authorities, health workers and local people) of the FMTs' response,was planned to get a clear picture of Strengths, Weaknesses/Gaps and Areas of Improvement that would be very important in making the response better in any future events of such scale when discussed and shared with all relevant stakeholders in Nepal. This documentation once shared with the international community would also help them learn from Nepal's experience. Methodology It was a multi-method study. Both quantitative and qualitative approaches were used to have an in-depth overview of the research question and the objectives set for the study. Records and reports relating Foreign Medical Team Coordination Committee (FMTCC) and meeting minutes of Health Emergency Operation Centre were reviewed. For feedback survey from foreign medical teams, the FMTCC Created the online questionnaire using Google forms® and Survey Monkey® (The initial feedback survey used Google forms and the second survey used Survey Monkey). Health workers involved in service delivery in different government and private health facilities participated in focused group discussions (FGDs) of health workers. Community members in most affected areas of the district participated in FGDs of the earthquake survivors. Health workers involved in service delivery with some managerial responsibility or key role in health facilities such as district health officers, medical superintendent, and emergency in-charge were considered for key informant interview (KIIs). Earthquake victims who sustained some injury or health problems during earthquake and received service from foreign medical team were selected for in-depth interviews (IDIs). Quantitative data were analyzed in Microsoft excel. Qualitative data were transcribed, coded and analyzed using thematic analysis technique manually. Findings Total of 8,962 deaths and 22,302 injuries occurred following earthquake of which 8,864 deaths and 21,156 injuries occurred in the most affected 14 districts of Nepal. In FGD and KIIs, most of the participants highlighted the earthquake had a huge impact on infrastructures. A large number of casualties were reported immediately after earthquake. Health facilities were overloaded with injured patients. Psychosocial problem like getting scared, forgetting things were also reported, although they were less common. In most cases, in district level, patients were treated on the ground in absence of adequate space or collapse of buildings of health facilities. Health workers were mobilized immediately after the earthquake with pooling of staffs from less affected areas or assigning double duty. One hundred and thirty-seven FMTs from 36 countries worked in Nepal to provide medical relief. Of the total FMTs providing relief work, 70% of the FMTs were from non-government and non-military agencies, 18% of the FMTs were from civilian government agencies and 12% from military agencies. Twenty percentage of the FMTs had the capacity of full field hospitals. Among the human resources in the FMTs, most of them were Doctor (42%) followed by allied health personal (23%), nurses (18%, logistic (9%) and administrative personnel (7%). Most of the FMTs were deployed in Kathmandu (18%) that had highest number of injuries (7,950) followed by Sindhupalchowk (18%) that had highest number of deaths (3,570). Most FMTs (48%) reported that information provided in the FMT coordination meeting before tasking was good. Regarding usefulness of information received at FMT coordination meeting (during operation), higher percentage shared that it was average (44%). Lack of preplanning and preparedness on disaster management was raised by research participants as one of the main challenge in dealing with post earthquake phase. Language barriers, lack of follow up, use of expired medicines in some cases, inadequate availability of equipments, differences in treatment procedures, inadequate orientation to local context and focus on publicity rather than the humanitarian efforts by some teams were the major issues in mobilization of and working with FMTs. Health workers stressed on the need of Planning and preparedness of disaster management including construction of earthquake resistant buildings for health facilities and activation of disaster team. Similarly, maintainance of adequate stock of basic logistics and appropriate manpower, training health workers on handling emergency cases, developing appropriate mechanism to mobilize health workers within country were the key suggestions for improvement of response in post disaster phase provided by health workers. Conclusion More than one fourth of the injured patients were in Kathmandu, followed by Sindhupalchowk, and significant numbers of injured patient were observed in Rasuwa, Dhading and Gorkha. Majority of the death were reported in Sindhupalchok followed by Kathmandu, Nuwakot and Rasuwa whereas most of the injured cases were reported in Kathmnadu district. To cater the health needs of Nepalese people in post disaster phase, one hundred and thirty-seven FMTs from 36 countries worked in Nepal to provide medical relief. Timely preparation and readiness of the procedures to handle the FMTs including their registration process, medical licensing procedures, procedures of coordinating mechanisms with the district, case management and treatment guidelines to be followed by the FMTs are crucial to have a better health sector response including that of FMTs.